Microbiome Research as an Effective Driver of Success Stories in Agrifood Systems – A Selection of Case Studies - Rocío Olmo; Rocío Olmo; Stefanie Urimare Wetzels; Stefanie Urimare Wetzels; Jaderson Silveira Leite Armanhi; Jaderson Silveira Leite Armanhi; Paulo Arruda; Paulo Arruda; Paulo Arruda; Gabriele Berg; Gabriele Berg; Gabriele Berg; et al. (Frontiers in Microbiology, 2022)
Increasing knowledge of the microbiome has led to significant advancements in the agrifood system. Case studies based on microbiome applications have been reported worldwide and, in this review, we have selected 14 success stories that showcase the importance of microbiome research in advancing the agrifood system. The selected case studies describe products, methodologies, applications, tools, and processes that created an economic and societal impact. Additionally, they cover a broad range of fields within the agrifood chain: the management of diseases and putative pathogens; the use of microorganism as soil fertilizers and plant strengtheners; the investigation of the microbial dynamics occurring during food fermentation; the presence of microorganisms and/or genes associated with hazards for animal and human health (e.g., mycotoxins, spoilage agents, or pathogens) in feeds, foods, and their processing environments; applications to improve HACCP systems; and the identification of novel probiotics and prebiotics to improve the animal gut microbiome or to prevent chronic non-communicable diseases in humans (e.g., obesity complications). The microbiomes of soil, plants, and animals are pivotal for ensuring human and environmental health and this review highlights the impact that microbiome applications have with this regard.